Cellulose Conversion to Sugar Alcohol by Solution Plasma Processing. Issue 1745 (16th September 2015) - Watthanaphanit, Anyarat; Lee, Hoonseung; Saito, Nagahiro
ABSTRACT: Cellulose was selectively converted to sugar alcohols (sorbitol and mannitol) over a supported-metal catalyst ruthenium on carbon (Ru/C) by the application of plasma in cellulose aqueous suspension. Generally, conversion of cellulose to sugar alcohol should be done under H2 pressure and high temperature. The goal of using solution plasma process (SPP) in this study is to initiate " self-hydrogenation " by reactive hydrogen species generated from the plasma due to dissociation of water medium. The sugar alcohols were produced at room temperature and atmospheric pressure. Electrospray ionization mass spectrometric analysis indicates that the SPP is a potent tool to promote the conversion of cellulose to sugar alcohols.